ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH MENGGUNAKAN TRANSAKSI NON TUNAI (ATM) PADA PT. BANK MANDIRI CABANG UNHAS - Izaac Lukas Dominggus Lawalata (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
The purpose of this study is to analyze the security and ease of users who can provide its own attractiveness for its users. Thus the use of ATM cards will provide a sense of security and convenience offered by PT. Bank Mandiri which makes the authors interested in analyzing and further know the big factors that affect the use of dominant transactions affect customers in using non-cash transactions, especially ATM cards at PT. Bank Mandiri Cabang UNHAS. The method used in this research is descriptive quantitative analysis using multiple linear regression analysis, using the program Statistic Program for Social Science (SPSS). The result of analysis shows that Security and Efficiency have positive and significant effect to the decision to use non-cash transactions at PT. Bank Mandiri Cabang Unhas.